Soft Masculinity Dalam Music Video NCT Dream “Hello Future" - Alya Syahputri (Jurnal Ilmu Komunikasi, 2022)
This study discusses the soft masculinity in NCT Dream's music video entitled "Hello Future". Soft masculinity itself is a concept of masculinity that does not leave the soft side in him but still shows his masculinity. Masculinity itself is a gender concept that is built by social construction which is generally aimed at men. The concept of soft masculinity has developed in line with developments in South Korea and is commonly used by Korean idols who combine feminine and masculine sides simultaneously. In the music video shown, the members wear clothes with bright colors and use various additional accessories. The background of the atmosphere also uses bright colors. In this study, to analyze the music video, a qualitative descriptive approach was used which is a description of the phenomenon that has been studied. This study also uses semiotic analysis proposed by Roland Barthes. Semiotic analysis does not examine the implicit in the music video, but up to the myths that exist in the music video. Roland Barthes's semiotic analysis uses the concepts of denotation, connotation, and myth. The results of this study indicate that in the music video, the members use the concept of soft masculinity. This is because the visualization that is displayed fulfills the elements that make up the concept of soft masculinity, namely Confucian masculinity, Japanese Bishonen masculinity, and Hollywood metrosexual masculinity.